PENINGKATAN LITERASI DIGITAL MASYARAKAT MELALUI SOSIALISASI INTERNET SEHAT DAN KEAMANAN DIGITAL DI KELURAHAN DURI KEPA - Bayu Waseso; Mubarak, Roy (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The advancement of information technology has encouraged society to increasingly rely on the internet in various aspects of life, from communication and access to information to economic activities. However, the high usage of the internet is also accompanied by low digital literacy among the community, particularly in terms of awareness of the dangers of negative content and digital security threats. This activity aims to improve the digital literacy of the community through healthy internet socialization and digital security education for the residents of Duri Kepa Village, West Jakarta. The method of conducting the activity was done face-to-face in the form of interactive presentations, open discussions, Q&A sessions, and simulations of real situations often faced by the community, such as online scams, data theft, and negative content for children. This activity was attended by 68 participants, consisting of groups of parents, teenagers, and environmental cadres. Parent participants gained an understanding of monitoring children's gadget use, teenage participants understood the importance of maintaining privacy and security of digital accounts, while environmental cadres acquired insights to disseminate information sustainably within their respective communities. The evaluation results show that most participants experienced an increase in understanding, marked by changes in scores before and after the activities as well as positive responses in group discussions. This activity concludes that community-based socialization with a practical and communicative approach can effectively raise public awareness about healthy and safe internet usage. Active involvement from residents is a key factor in the success and sustainability of digital education programs in the local community.